(3chcH GdeHGfi hehcH GdeYGfi aj TQM UdhGJ YHO GdbGOQ GdcjdGfis - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hcai , hSdGe Ydi YHGOg GdPjf EUWai CeG HYO agPG TQM dWja hSQM dWja GdNjGd GdeWja cTa Hg YHO GdZfi eG JVefg GdeJf ef cd eYfi Sfi s
(3BNQgG (B:s
(3dGRGd QVhGf GdEdg jNUg hjYeg HGdLhO hGdEMSGf eG QGb ef YHO GdZfi eOjMI deMHg HJYGbH GdedhGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B394s
Keywords: (3GdJUha hGdBOGH GdTQYjIs